IDphy An International Online Resource for Molecular and Morphological Identification of Phytophthora - Abad, Z Gloria (Plant disease, 2023)
Phytophthora, with 203 species, is a genus of high importance in agriculture worldwide. Here, we present the online resource "IDphy", developed to facilitate the correct identification of species of Phytophthora using the type specimens from the original descriptions wherever possible. IDphy emphasizes species of high economic impact and regulatory concern for the United States. IDphy presents an interactive Lucid key and a tabular key for 161 culturable species described as of May 2018, including 141 ex-types and 20 well-authenticated specimens. IDphy contains standard operating procedures for morphological and molecular characterization, as well as a glossary, image gallery, and numerous links. Each of the 161 factsheets includes access to nomenclature and morphological and molecular features, including sequences of the internal transcribed spacer ribosomal DNA, cytochrome C oxidase subunit I (barcoding genes), YPT1, β-tubulin, elongation factor 1a, L10, heat shock protein 90, and other genes. IDphy contains an innovative in silico BLAST and phylogenetic sequence analysis using NCBI. The IDphy mobile app, released in August 2021 (free for Android or iOS), allows users to take the Lucid key into the laboratory. IDphy is the first online identification tool based on the ex-types implemented for plant pathogens. In this article, we also include information for 21 new species and one hybrid described after the publication of IDphy, the status of the specimens of the types and ex-types at international herbaria and culture collections, and the status of genomes at the GenBank (currently 153 genome assemblies which correspond to 42 described species, including 16 ex-types). The effectiveness of the IDphy online resource and the content of this article could inspire other researchers to develop additional identification tools for other important groups of plant pathogens